Cytokines, antibodies, and histopathological profiles during Giardia infection and variant-specific surface proteinbased vaccination - Serradell, Marianela del Carmen. (2018)
Giardiasis is one of the most common human intestinal diseases worldwide. Several experimental animal models have been used to evaluate Giardia infections, with gerbils (Meriones unguiculatus) being the most valuable model due to their high susceptibility to Giardia infection, abundant shedding of cysts, and pathophysiological alterations and signs of disease similar to those observed in humans. Here, we report cytokine and antibody profiles both during the course of Giardia infection in gerbils and after immunization with a novel oral vaccine comprising a mixture of purified variant-specific surface proteins (VSPs). Transcript levels of representative cytokines of different immune profiles as well as macro- and microtissue alterations were assessed in Peyer's patches, mesenteric lymph nodes, and spleens. During infection, cytokine responses showed a biphasic profile: an early induction of Th1 (gamma interferon [IFN-γ], interleukin-1β [IL-1β], IL-6, and tumor necrosis factor [TNF]), Th17 (IL-17), and Th2 (IL-4) cytokines, together with intestinal alterations typical of inflammation, followed by a shift toward a predominant Th2 (IL-5) response, likely associated with a counterregulatory mechanism. Conversely, immunization with an oral vaccine comprising the entire repertoire of VSPs specifically showed high levels of IL-17, IL-6, IL-4, and IL-5, without obvious signs of inflammation. Both immunized and infected animals developed local (intestinal secretory IgA [S-IgA]) and systemic (serum IgG) humoral immune responses against VSPs; however, only infected animals showed evident signs of giardiasis. This is the first comprehensive report of cytokine expression and anti-Giardia antibody production during infection and VSP vaccination in gerbils, a reliable model of the human disease.